Analisis Framing Pemberitaan Kasus Kekerasan Seksual Murid SD Oleh Driver Ojol Di Serang Banten Pada Media Online Radar Banten dan Detikcom - Ayu Nurmala; Arfian Suryasuciramdhan; Siti Abelia Puteri; Siti Indriyani Putri (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This research discusses the phenomenon of sexual violence against children in Indonesia with a focus on a case involving an elementary school student in Serang, Banten. Through a framing analysis approach, this research explores how the media, especially Detik.com and Radar Banten, frame news about the case. The research results show that psychological, social and environmental factors influence perpetrators of sexual violence in targeting minors or their own children. The framing of reports by the media also plays an important role in shaping public perceptions about the case, by highlighting aspects such as the perpetrator's psychological condition, the role of parents, and the urgency in handling sexual violence cases. The implications of this research are the importance of a deeper understanding of the dynamics of the relationship between perpetrators and victims of sexual violence, as well as the need for preventive measures and stronger law enforcement to protect children from sexual violence.